Manufacturability analysis and process planning for additive and subtractive hybrid manufacturing of Quasi-rotational parts with columnar features. (January 2020) - Chen, Li; Lau, Tak Yu; Tang, Kai
Abstract: The newly emerged hybrid manufacturing platform that incorporates both additive manufacturing (AM) and five-axis machining modules makes it possible to manufacture parts of complex shapes with high finish-surface quality that are impossible to be produced solely by either machining or additive manufacturing. In general, a hybrid manufacturing process is signified by an alternating sequence of AM operations and machining operations that alternatingly build and machine an in-process workpiece into the final design shape. Aside from other considerations, collision avoidance between the in-process workpiece and both the cutting tool and the material-dispensing nozzle is one of the most critical constraints that affect the determination of the alternating sequence. Due to the newness of hybrid manufacturing technology, currently there has been few systematic studies of this collision avoidance problem in which the obstacles are in a constant state of growing, especially on nozzle collision avoidance which – though never an issue in the traditional 2.5-axis AM because the in-process workpiece is always below the printing nozzle – now becomes a real concern in hybrid manufacturing as the in-process workpiece now dynamically grows and is not constrained by the current build layer. The nozzle collision problem is particularly pronounced in metallic hybrid manufacturing where the nozzle compartment typically is large and has a complex shape. In this paper, we conduct a thorough study of this collision avoidance problem in hybrid manufacturing and present a deterministic algorithm for automatically generating a collision-free sequence of hybrid manufacturing with the least alternations for a solid part. Specifically, as long as the part can be represented in the so-called columnar form, and the build layers are either planar or on concentric conic surfaces, for any given tool and nozzle, our algorithm will automatically generate an alternating sequence of minimum length whose corresponding hybrid manufacturing process is guaranteed to be free of collision with either the tool or nozzle The columnar representation actually embodies a large class of industrial parts such as aero-engine blisks and gears while concentric conic build layers are the most common type of slicing strategy adopted in multi-axis 3D printing. Ample computer simulation tests of the proposed algorithm are performed and the results confirm the correctness and effectiveness of the proposed algorithm. Graphical abstract: Highlights: The definition and its calculation of a new metric of manufacturability are given. A deterministic search method is given to solve the hybrid process planning problem. Proof that the method is able to produce the fewest hybrid alternations is provided. Simulation is conducted and the results show that collision is strictly avoided.